PENGARUH LATAR BELAKANG PENDIDIKAN DAN PENGALAMAN KERJA TERHADAP ETOS KERJA KARYAWAN PT. PAN BROTHERS TBK SRAGEN. - Budiwinarto, Kim; Arifin, Ahmad Nur; Sulistya, Sulistya (Surakarta Management Journal, 2024)
This study aims to determine the effect of educational background and work experience on the work ethic of PT. PAN Brothers Tbk Sragen either partially or simultaneously. The hypothesis in this study is that educational background and work experience influence the work ethic of PT. PAN Brothers  Tbk Sragen either partially or simultaneously. This research is a survey research with a quantitative research type. The data used in this study uses primary data from the results of the respondents' questionnaire answers. The research population is all employees at PT. PAN Brothers Tbk Sragen with a sample of 110 people. The analysis technique used is multiple linear regression test, t test, F test, and test the coefficient of determination. The results of the study draw the conclusion that educational background and work experience have a significant effect on the work ethic of PT. PAN Brothers Tbk Sragen either partially or simultaneously.